Border women and the community of Maclovio Rojas autonomy in the spaces of neoliberal neglect - Téllez, Michelle (University of Arizona Press, 2021)
"This is a book about hope, struggle, and possibility in the context of gendered violences of racial capitalism on the Mexican side of the U.S.-Mexico border"--